Adaptive Curriculum Development Model Based On Outcome-Based Education In The Digital Transformation Era - Muhamad Yani; Akhmad Syahri; Mustain (International journal of technology and education research, 2026)
This study aims to analyze the model of adaptive curriculum development based on Outcome-Based Education (OBE) in the era of digital transformation and to identify the challenges and implementation strategies relevant to modern education. The study employed a qualitative approach using a library research method through the analysis of scientific articles, educational policy documents, academic books, and previous studies related to curriculum development, digital transformation, and OBE published between 2020 and 2025. Data were collected through documentation and literature review techniques and analyzed using the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The findings reveal that adaptive curriculum development based on OBE emphasizes strengthening 21st-century competencies, integrating digital technology, project-based learning, and flexibility in learning outcomes. The study also found that digital transformation in curriculum development still faces several obstacles, including limited digital competence among educators, resistance within academic culture, and unequal technological infrastructure in educational institutions. The findings contribute theoretically to the development of adaptive curriculum concepts integrated with the perspectives of society 5.0 and digital transformation. Practically, the study may serve as a reference for educational institutions and policymakers in designing innovative, flexible, and globally relevant education systems.